Organ Preservation Treatment for Clinical T1bN0M0 Thoracic Esophageal Squamous Cell Carcinoma: A Long-Term Outcome Analysis of Radical Esophagectomy vs. Definitive Chemoradiotherapy - Zhao, Hongbo; Koyanagi, Kazuo; Kato, Ken; Ito, Yoshinori; Itami, Jun; Igaki, Hiroyasu; Tachimori, Yuji (Medicine and Medical Research: New Perspectives Vol. 10, 2024)
Background: For patients with clinical T1aN0M0 thoracic esophageal squamous cell carcinoma (ESCC), endoscopic submucosal dissection (ESD) or endoscopic mucosal resection (EMR) are the standard treatment modalities. For patients with clinical staging higher than clinical T1aN0M0 thoracic ESCC, surgery alone, chemotherapy, radiotherapy, or concurrent chemoradiotherapy are the standard treatment options. For patients with clinical T1aN0M0 thoracic ESCC, surgery is currently the recommended clinical treatment, but surgery may entail potential risks and loss of organ function. Therefore, the study conducted a retrospective analysis comparing the long-term outcomes of patients with clinical T1bN0M0 thoracic ESCC treated with radical esophagectomy to those treated with definitive chemoradiotherapy (dCRT). Methods: A total of 320 consecutive patients with clinical T1bN0M0 thoracic ESCC who initially underwent radical esophagectomy or chemoradiotherapy during 2001–2011 were deemed eligible. Of these patients, 102 and 218 underwent radical esophagectomy and dCRT, respectively. Overall survival (OS) and causes of death were compared between the esophagectomy group and the chemoradiotherapy group. Results: Five-year OS in the esophagectomy group was significantly better than that of the chemoradiotherapy group in both the overall sample and a subset of patients aged ³70 years (P=0.004 and P=0.040). Male patients appeared to benefit more from radical esophagectomy (P=0.005). Until 2006, radical esophagectomy yielded superior results relative to dCRT (P=0.009). However, the survival outcomes after chemoradiotherapy were non-inferior to those after esophagectomy since 2007 (P=0.255). Up to 2006, esophagectomy and chemoradiotherapy groups exhibited significant differences in the causes of death (P=0.024), such that the latter group had a significantly higher rate of deaths due to respiratory complications (P=0.025). However, the introduction of 3-dimensional radiation with CT-guided planning in 2007 resolved this inter-group difference (P=0.460). The SANO study's findings in organ preservation in esophageal cancer have spurred further research into more organ-sparing treatment strategies for esophageal cancer and have provided patients with a new therapeutic option. Conclusions: Significant advancements in radiation technology have facilitated comparable long-term outcomes for patients with clinical T1bN0M0 thoracic esophageal squamous cell carcinoma (ESCC) in the chemoradiotherapy group, rivaling those of the esophagectomy group. In recent years, the increasingly prominent role of immunotherapeutic drugs in the treatment of esophageal squamous cell carcinoma has made organ preservation an increasingly viable option for early-stage esophageal cancer. The SANO clinical study from the Netherlands, which has achieved notable results in organ-sparing strategies for esophageal cancer, has propelled further research into esophageal organ preservation treatment approaches. This progress also offers patients a novel therapeutic alternative.